STRENGTHENING RELIGIOUS EDUCATION FOR FAMILY RESILIENCE IN YOGYAKARTA MUSLIM MINORITIES - Yusron Masduki; Hanif Cahyo Adi Kistoro; Sutipyo Ru’iya; Sutarman Sutarman; Sukirman Sukirman (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
Family resilience is very important for minority Muslim societies. The family and environmental factors become the main thing. The role of parent and community leaders is one of the keys to the success of strengthening religious aspects for minority Muslims. This research will seek to answer the questions about how to strengthen religious education for family security among minority Muslims. This research approach used a descriptive narrative. It related the life experience of a person or group which was important data of explaining the meaning of the phenomenon to be studied. The participants of this research were the parents and community leaders of Banjarasri Kulon Progo village of Yogyakarta which total were 12 persons. The data collection techniques used: (1) observation; (2) in-depth interviews. Data analysis used analytical coding, where this analysis described the story, chronologically the events that become a turning point with the stages of data organization, reading, describing data in codes and themes, classification of data, interpreting data, and presenting data. The research findings related to strengthening the values of religious education in Muslim minority families carried out in three ways, namely: (1) strengthening in the field of creed and morals; (2) strengthening in education, and (3) strengthening in economics.